Effect of lead sintering aid to TiO2 photoanode for flexible dye sensitized solar cell - Hazim, Khir; Pandey, Adarsh Kumar; Saidur, Rahman Md; Muhammad Shakeel, Ahmad; Dewika, M.; Samykano, Mahendran (Institute of Physics, 2023)
The commercial application of flexible dye sensitized solar cells (DSSCs) is somewhat limited due to the devices’ low conversion efficiency. The low sintering temperature in preparing the photoanode has caused poor interparticle contact, low charge transfer and low efficiency. Hence, this research aims to improve the interparticle contact of titanium dioxide (TiO2) photoanode with the novel use of lead (Pb) nanoparticles as sintering aid at low temperature. TiO2-Pb composite photoanode was prepared with different composition of Pb including 4% and 7% sintered at low temperature of 250°C. The research discovered that TiO2 photoanode mixed with 4% Pb composition showed the lowest charge transfer resistance (RCT) even at low sintering temperature. The RCT value was even lower than a commercial TiO2 photoanode sample that was sintered at 450°C. The addition of Pb sintering aid has improved interparticle contact in the photoanode via the neck formation at the TiO2-Pb interface and enhanced charge transfer despite the low temperature. The prepared photoanode samples displayed potential in developing highly efficient flexible DSSC.